Combined Treatment with Amlodipine and Atorvastatin Calcium Reduces Circulating Levels of Intercellular Adhesion Molecule-1 and Tumor Necrosis Factor-α in Hypertensive Patients with Prediabetes - Huang, Zhouqing; Chen, Chen; Li, Sheng; Kong, Fanqi; Shan, Peiren; Huang, Weijian (Frontiers in Aging Neuroscience, 2016)
Amlodipine and atorvastatin combination reduces levels of ICAM-1 and TNF-α in hypertensive prediabetes Abstract Objective: To assess the effect of amlodipine and atorvastatin on intercellular adhesion molecule (ICAM)-1 and tumor necrosis factor (TNF)-α expression, as endothelial function and inflammation indicators, respectively, in hypertensive patients with and without prediabetes. Methods: Forty-five consecutive patients with hypertension, diagnosed according to JNC7, were divided into two groups based on the presence (HD group, n=23) or absence (H group, n=22) of prediabetes, diagnosed according to 2010 ADA criteria, including impaired glucose tolerance and fasting glucose. All patients simultaneously underwent 12-week treatment with daily single-pill amlodipine besylate/atorvastatin calcium combination (5/10mg; Hisun-Pfizer Pharmaceuticals Co. Ltd). Serum isolated before and after treatment from overnight fasting blood samples was analyzed by ELISA. Results: In the HD and H groups after vs. before 12-week amlodipine/atorvastatin treatment, there were significantly (all P <.01) lower levels of ICAM-1 (3.06 ± 0.34 vs. 4.07 ± 0.70 pg/ml; 3.26 ± 0.32 vs. 3.81 ± 0.60 pg/ml, respectively) and TNF-α (78.71 ± 9.19 vs. 110.94 ± 10.71 pg/ml; 80.95 ± 9.33 vs. 101.79 ±11.72 pg/ml, respectively), with more pronounced reductions in HD vs. H group (ICAM-1Δ: 1.01 ± 0.80 vs. 0.55 ± 0.64 pg/ml, respectively, P = 0.037; TNF-αΔ: 32.23 ± 14.33 vs. 20.84 ± 14.89 pg/ml, respectively, P= 0.011), independently from blood pressure and cholesterol level reduction. Conclusions: Amlodipine/atorvastatin improved endothelial function and inflammation, as reflected by lower circulating levels of ICAM-1 and TNF-α, more prominently in hypertensives with than without prediabetes. Starting statin treatment before overt diabetes in hypertensives thus might improve cardiovascular outcomes. Keywords: Amlodipine and atorvastatin calcium; prediabetes; hypertension; inflammation; endothelial dysfunction; intercellular adhesion molecule-1; tumor necrosis factor-α